Phalange metastasis from carcinoma of alveolus - Shrivastava Rajeev; Singh K; Umbarker B; Karle R; Shrivastava M (Indian Journal of Dental Research, 2009)
Metastatic involvement of a phalanx by head and neck cancers is rare. We report a case of a 66-year-old man with squamous cell carcinoma of the alveolus who had no residual disease or local recurrence after treatment but presented with metastasis to the middle phalanx of the middle finger.